2003
DOI: 10.1088/1126-6708/2003/09/061
|View full text |Cite
|
Sign up to set email alerts
|

Type-IIB colliding plane waves

Abstract: Four-dimensional colliding plane wave (CPW) solutions have played an important role in understanding the classical non-linearities of Einstein's equations. In this note, we investigate CPW solutions in 2n+2-dimensional Einstein gravity with a n+1-form flux. By using an isomorphism with the four-dimensional problem, we construct exact solutions analogous to the Szekeres vacuum solution in four dimensions. The higher-dimensional versions of the Khan-Penrose and Bell-Szekeres CPW solutions are studied perturbativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The higher dimensional generalization of the 4-dimensional Bell-Szekeres solution with a n-form potential (by which we mean m = n and non-dilatonic) has been considered recently by Gutperle and Pioline in [18]. They found for their solution n 1 = 2n/(2n − 1) < 2 for n > 1 and that R 2 blows up at the junction.…”
Section: Physical Flux-cpw Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher dimensional generalization of the 4-dimensional Bell-Szekeres solution with a n-form potential (by which we mean m = n and non-dilatonic) has been considered recently by Gutperle and Pioline in [18]. They found for their solution n 1 = 2n/(2n − 1) < 2 for n > 1 and that R 2 blows up at the junction.…”
Section: Physical Flux-cpw Solutionmentioning
confidence: 99%
“…As we will demonstrate in section 4, the later solutions however violate the OS junction conditions and are thus not acceptable. Recently, Gutperle and Pioline [18] has tried to construct the CPW in 10-dimensional IIB string theory with the self-dual form flux; for latter convenience, we call the general CPW with form flux the "flux-CPW". However, they found that the curvature invariants blow up at the junction so that the solutions cannot be used to describe the flux-CPW.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], Gurses et.al discussed the CPW solutions in dilaton gravity, in higher dimensional gravity, and in higher dimensional Einstein-Maxwell theory. In [11], Gutperle and Pioline tried to construct the CPW solutions in the ten-dimensional gravity with self-dual form flux. However, their generalized BS-type solution (3.37) fails to satisfy the junction condition and is unphysical.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors addressed themselves to the more general problem but they obtained only perturbative and singular solutions. 23,24…”
Section: Colliding "P +2…-forms In "P +4…-dimensionmentioning
confidence: 99%